Cell culture propagation of foot-and-mouth disease virus: adaptive amino acid substitutions in structural proteins and their functional implications - Dill, Veronika (Virus Genes, 2019)
Foot-and-mouth disease is endemic in livestock in large parts of Africa and Asia, where it is an important driver of food insecurity and a major obstacle to agricultural development and the international trade in animal products. Virtually all commercially available vaccines are inactivated whole-virus vaccines produced in cell culture, but the adaptation of a field isolate of the virus to growth in culture is laborious and time-consuming. This is of particular concern for the development of vaccines to newly emerging virus lineages, where long lead times from virus isolate to vaccine can delay the implementation of effective control programs. High antigen yields in production cells are also necessary to make vaccines affordable for less developed countries in endemic areas. Therefore, a rational approach to cell culture adaptation that combines prior knowledge of common adaptive mutations and reverse genetics techniques is urgently required. This review provides an overview of amino acid exchanges in the viral capsid proteins in the context of adaptation to cell culture. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11262-019-01714-7) contains supplementary material, which is available to authorized users.